STING induces ZBP1-mediated necroptosis independently of TNFR1 and FADD - Konstantinos Kelepouras; Julia Saggau; Debora Bonasera; Christine Kiefer; Federica Locci; Hassan Rakhsh-Khorshid; Louisa Grauvogel; Ana Beatriz Varanda; Martin Peifer; Elena Loricchio; Antonella Montinaro; Marijana Croon; et al. (Nature, 2025)
Abstract Conditional deletion of caspase-8 in mouse epidermal keratinocytes ( Casp8 E-KO ) causes necroptosis-driven lethal dermatitis 1–7 . Here we find that the loss of Casp8 leads to an accumulation of cytosolic DNA that is responsible for the activation of a cyclic GMP-AMP synthase (cGAS)–stimulator of interferon genes (STING)-mediated transcriptional program. Genetic and biochemical evidence indicate that STING upregulates both Z-DNA-binding protein 1 (ZBP1) and mixed lineage kinase domain-like pseudokinase. Combined caspase-8-deficiency- and STING-activation-driven accumulation of Z-nucleic acids activates ZBP1 and triggers the formation of a ZBP1–RIPK1–RIPK3 complex independently of the FADD–RIPK1–RIPK3 complex, enabling execution of necroptosis. Genetically, we reveal a functional overlap between STING and ZBP1 as drivers of lethal dermatitis independently of tumour necrosis factor receptor 1 (TNFR1), identifying an aetiology of necroptotic inflammation. As gain-of-function mutations in human STING cause STING-associated vasculopathy with onset in infancy (SAVI), we assessed the role of STING-induced necroptosis in SAVI’s aetiology. Chronic activation of STING in patients orchestrates a necroptotic transcriptional program that is confirmed in the Sting1 N153S SAVI preclinical mouse model in which immune-cell-driven pathology and lethality are rescued by receptor-interacting serine/threonine-protein kinase 3 ( Ripk3 ) co-deletion. These findings establish STING-driven ZBP1-mediated necroptosis as a central pathogenic mechanism in both caspase-8-deficient inflammation and SAVI and suggest that targeting the ZBP1–RIPK3–MLKL axis holds therapeutic potential for interferonopathies characterized by excessive necroptosis.